Heat transfer in fractal materials. (February 2016) - Tarasov, Vasily E.
Highlights: Heat transfer in fractal materials is described by models with non-integer dimensional spaces. Solutions of heat transfer equation of fractal materials are suggested. The steady heat flow in fractal pipe and rod are described. Abstract: Heat transfer in fractal materials is considered in the framework of continuous models with non-integer dimensional spaces. We use a recently proposed vector calculus in non-integer dimensional spaces to describe heat flow in fractal materials. Solutions of the steady heat flow in fractal pipe and rod are derived.